2018
DOI: 10.3892/etm.2018.6198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transplantation of cardiac stem cells overexpressing integrin‑linked kinase on cardiac function of rats with acute myocardial infarction

Abstract: In the present study, we aimed to investigate the effect of transplantation of cardiac stem cells (CSCs) overexpressing integrin-linked kinase (ILK) on cardiac function of rats with acute myocardial infarction (MI). A total of 60 rats were randomly divided into normal saline (NS) group (n=20), green fluorescent protein (GFP)-CSC group (n=20) and ILK-CSC group (n=20). In the ILK-CSC group, CSCs in rats were transfected with GFP adenovirus vector overexpressing ILK. The rat model of MI was established. The cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, ILK can act as a pro-survival factor and play a role in protecting cells from high glucose-associated apoptosis and oxidative stress [ 24 , 25 ]. Overexpression of ILK can promote proliferation and vascular differentiation of stem cells and improve muscular function [ 26 ]. We have previously found that overexpression of ILK enhances the regeneration of native smooth muscle cells and improves muscle contractile function [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ILK can act as a pro-survival factor and play a role in protecting cells from high glucose-associated apoptosis and oxidative stress [ 24 , 25 ]. Overexpression of ILK can promote proliferation and vascular differentiation of stem cells and improve muscular function [ 26 ]. We have previously found that overexpression of ILK enhances the regeneration of native smooth muscle cells and improves muscle contractile function [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, our mice model exhibited normal levels of myocardial ILK expression. In addition, a number of preclinical studies reported the effect of ILK-MSCs on myocardial infarction using mouse, rat and porcine animal models, which evidenced a sizable reduction in infarct size and fibrosis, and significant improvement in regional perfusion and vessel density when compared with vector-MSCs [ 28 , 30 , 56 ]. It is possible to speculate that ILK-MSC used in preclinical models to reduce infarct size may also differentiate into ECs, restoring ILK levels in coronary endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin Linked Kinase (ILK) is a serine/threonine kinase that binds to the cytoplasmic domain of β-integrins and participates in cardiac remodelling after MI [ 30 , 56 ]. ILK lies upstream of many intracellular signalling pathways potentially involved in such effect, including angiogenesis, mechanotransduction, extracellular matrix-mediated signalling, cell survival, proliferation, differentiation and apoptosis [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…ILK inhibition attenuated the induced hypertrophy ( Lu et al, 2006 ). In contrast, ILK overexpression has been implicated in myocardial infraction, a disease that leads to heart failure resulted from myocardial cell death ( Zhang and Guo, 2018 ). Transplanting cardiac stem cells overexpressing ILK restores cell death and cardiac function in a mouse model of this disease ( Zhang and Guo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ILK overexpression has been implicated in myocardial infraction, a disease that leads to heart failure resulted from myocardial cell death ( Zhang and Guo, 2018 ). Transplanting cardiac stem cells overexpressing ILK restores cell death and cardiac function in a mouse model of this disease ( Zhang and Guo, 2018 ). Furthermore, the mouse Alzheimer’s disease model displays a decrease in ILK expression, whereas its overexpression rescues hippocampal neurogenesis and defects in memory via the downstream signaling pathway, Akt/GSK3β ( Xu X.F.…”
Section: Introductionmentioning
confidence: 99%